Factors influencing job satisfaction of private commercial bank- employees in Bangladesh - E-Alam, Md. Faisal; Anis, Zohurul; Haque, A. K. M. Ahasanul; Kabir, SMH; Karim, Md Wasiul; Ulfy, Mohammad Arije (Southern Academic Publisher, 2022)
This paper seeks to determine, explore and examine the factors affecting the job satisfaction of private commercial bank-employees in Bangladesh. A qualitative research design was employed to collect data from bank employees (n = 5) through in-depth semi-structured interviews and a focus group discussion (n=5). For the validity and reliability of the tool, the interview protocol was checked, discussed, refined and finalized. A thematic analysis was used to extract themes and subthemes that identifies the influ- encing factors for job satisfaction of private commercial bank employees and their attitudes towards satisfaction. Overall, the findings show that, employees have positive attitudes about their job because of enjoying some determinants of job satisfaction such as working environment, interpersonal relation- ship, financial remuneration, promotion and training and development facilities. The study discusses practical implications as well as future research direction. Therefore, it can be concluded that the re- spective bank authorities should be of highly concerned as to increase the values/standards of the job satisfaction determinants which have positive impact on the overall job satisfaction.